2008
DOI: 10.1016/j.neuron.2008.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Mutant Prion Protein Expression Causes Motor and Memory Deficits and Abnormal Sleep Patterns in a Transgenic Mouse Model

Abstract: A familial form of Creutzfeldt-Jakob disease (CJD) is linked to the D178N/V129 prion protein (PrP) mutation. Tg(CJD) mice expressing the mouse homolog of this mutant PrP synthesize a misfolded form of the mutant protein, which is aggregated and protease resistant. These mice develop clinical and pathological features reminiscent of CJD, including motor dysfunction, memory impairment, cerebral PrP deposition, and gliosis. Tg(CJD) mice also display electroencephalographic abnormalities and severe alterations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
127
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(140 citation statements)
references
References 52 publications
12
127
0
1
Order By: Relevance
“…Golgi-In primary neurons and non-neuronal cell lines, PrP molecules carrying pathogenic mutations start aggregating soon after biosynthesis in the ER and accumulate in intracellular organelles (7,14,15). Consistent with previous observations (14), D177N/Met-128 PrP expressed in N2a cells acquired distinctive biochemical characteristics of pathogenic PrP, such as insolubility in non-denaturing detergents (supplemental Fig.…”
Section: D177n/met-128 Prp Is Retained In Er Andsupporting
confidence: 89%
See 1 more Smart Citation
“…Golgi-In primary neurons and non-neuronal cell lines, PrP molecules carrying pathogenic mutations start aggregating soon after biosynthesis in the ER and accumulate in intracellular organelles (7,14,15). Consistent with previous observations (14), D177N/Met-128 PrP expressed in N2a cells acquired distinctive biochemical characteristics of pathogenic PrP, such as insolubility in non-denaturing detergents (supplemental Fig.…”
Section: D177n/met-128 Prp Is Retained In Er Andsupporting
confidence: 89%
“…In line with this view, ER accumulation of mutant PrP and alteration of ER morphology have been found in the CNS of a transgenic mouse model of fCJD (15). However, further studies are needed to decipher the cellular and molecular pathways activated by mutant PrPs that ultimately result in neuronal dysfunction and degeneration.…”
mentioning
confidence: 83%
“…This PrP shows similarities to PrP Sc and is detergent insoluble, yielding a PrP 27-30 fragment (154). Similar findings were obtained with Tg mice overexpressing the murine homologue of the P102L mutation associated with GSS syndrome (151) and in Tg mice overexpressing the murine homologue of the D178N/V129 mutation associated with familial CJD (155). Additional studies overexpressing wild-type PrP C in Tg mice demonstrated that such mice develop a type of neurodegeneration clinically manifested as paresis and tremor.…”
Section: Toxicity and Infectivity Of Prion Protein Aggregatessupporting
confidence: 68%
“…Serial passage of brain homogenates to Tg mice expressing lower levels of the same transgene accelerated the onset of disease ). As models of FFI and fCJD in humans, Tg mice expressing D178N coupled with M129 and V129, respectively, show behavioral abnormalities, misfolded PrP, and neuropathological changes (Dossena et al 2008;Jackson et al 2009). Mice overexpressing a novel set of mutations (S170N/N174T) engineered to alter the structure of PrP also developed disease, which transmitted to animals expressing wt PrP (Sigurdson et al 2009 (Cohen et al 1994).…”
Section: Transgenic Micementioning
confidence: 99%